Vocational education and training in Greece : short description - (:unkn) unknown (Publications Office of the European Union, 2014)
This overview of the vocational education and training system in Greece is published during the fifth Greek Presidency of the Council of the EU (first half of 2014). It forms part of the series of short descriptions regularly published by Cedefop on national VET systems. The 2014 Greek EU Presidency takes place at a time of major economic and social challenges, as the crisis, which can be felt all over Europe, has hit Greece especially hard. Whereas past reforms have so far focused on economic issues, recent initiatives aim to make VET more attractive in a country where the worlds of education and training and work have been quite apart. The 2013 legislation on secondary education aims to reinforce work-based components of education and training. The action plan for youth employment intends to better link education with work, upgrade VET, boost apprenticeship and broaden career guidance offered to young people. (BIBB-Doku)
Keywords: S System beruflicher Bildung; S 2.3 Berufsbildungspolitik; S 1.3 Berufliche Erstausbildung; S 1.5.2 Berufliche Weiterbildung; G 1.2 Arbeitsmarkt; L 5 Beratung & Orientierung; I 2.2.1 Westeuropa; Berufsbildungssystem; Berufsbildungspolitik; Berufsausbildung; Berufliche Weiterbildung; Arbeitsmarkt; Früherkennung; Berufsberatung; Griechenland